1994
DOI: 10.1097/00000658-199406000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Interferon–Alpha-2a for the Treatment of Complex Hemangiomas of Infancy and Childhood

Abstract: ObjectiveThe authors describe the use of interferon-alpha-2a in the treatment of complex hemangiomas and review the role of interferon (IFN) in this example of an angiogenic disease. Summary Background DataHemangiomas are the most frequent tumors of infants and children. They grow rapidly for 6 to 8 months and then resolve over a period of years. Approximately 5% produce life-, sight-, or limbthreatening complications, with mortality rates between 20% and 50%. Aggressive therapy with steroids, arterial ligati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
11

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(39 citation statements)
references
References 28 publications
2
26
0
11
Order By: Relevance
“…This syndrome has a similar ultrasonographic appearance to the vascular lesions with hemangiolymphangioma 14,15 , but the latter is not associated with asymmetric limb hypertrophy. Hemangiolymphangioma can now be treated effectively by OK-432 and interferon-alfa-2a [5][6][7][8][9][10] . Ogita et al 6 suggested that the intratumoral injection of OK-432 induces and activates white blood cells, and elevated cytokines (including tumor necrosis factor) increase the endothelial permeability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This syndrome has a similar ultrasonographic appearance to the vascular lesions with hemangiolymphangioma 14,15 , but the latter is not associated with asymmetric limb hypertrophy. Hemangiolymphangioma can now be treated effectively by OK-432 and interferon-alfa-2a [5][6][7][8][9][10] . Ogita et al 6 suggested that the intratumoral injection of OK-432 induces and activates white blood cells, and elevated cytokines (including tumor necrosis factor) increase the endothelial permeability.…”
Section: Discussionmentioning
confidence: 99%
“…The accelerated lymph drainage and increased lymph flows lead to shrinkage of the cystic spaces. Ricketts et al 8 demonstrated that interferon-alfa inhibits angiogenesis, and endothelial cell migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O alfa-2a-interferon tem sido utilizado com ótimos resultados no tratamento dos hemangiomas 7,[10][11][12][13][14][15] . Isso levou Reinhardt e cols.…”
Section: Discussionunclassified
“…Estudos in vivo, em modelos animais, com linfócitos e angiogênese induzida por células tumorais, o a-2a-INF demonstrou também atuar indiretamente, inibindo o estímulo angiogênico, através da inibição dos efeitos de fatores de crescimento específicos sobre a proliferação de células endoteliais 12,13 .…”
Section: Discussionunclassified